Strategi Negara Anggota ASEAN dalam Menghadapi Cina di Laut Cina Selatan - , LADY MAHENDRA, Prof. Dr. Mohtar Masâoed ([Yogyakarta] : Universitas Gadjah Mada, 2014)
South China Sea area is becoming a platform of power competition between China, The Philippines, Vietnam, Malaysia, and Brunei. Five parties mentioned above are competing over sovereignty in certain areas of the South China Sea. Basically, the issue in the South China Sea area is quite similar to other territorial disputes. The difference is just that this area is located on such strategic position which became the factor that drives more public attention to this case. Along with the emergence of colonialism concept, South China Sea area which at first no one took notice, suddenly became interesting to certain parties, considering its strategic value for expansive policy. In the contemporary era, the rise of this conflict perceived as a problem which caused by shifting balance of power, that happened when the U.S. sought to preserve its unilateral moment after the end of cold war. This lead to vacuum of power situation in the Southeast Asia, thus encourage China to build up presence in the dispute area. This paper discuss about the strategies of each ASEAN member states towards China related to the dispute in the South China Sea. Even though there are only 4 ASEAN countries that directly involved, however the adoption of the Declaration on the South China Sea by all ASEAN member countries, asserted that in this case ASEAN is standing together to show their objections of Chinaâs aggressiveness. With structural realism perspective as the analysis tool, tendencies of ASEAN member statesâ different strategies are understandable by the explanation about motives behind it. Which Philippines and Vietnam tend to leaning towards balancing strategy, and then Cambodia, Laos, and Myanmar indicate towards bandwagoning strategy, while the rest of the members did not show tendencies of leaning either ways.